2020
DOI: 10.1161/circulationaha.119.043100
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Trends, and Outcomes of Type 2 Myocardial Infarction in a Community Cohort

Abstract: Background: Type 2 myocardial infarction (T2MI) occurs because of an acute imbalance in myocardial oxygen supply and demand in the absence of atherothrombosis. Despite being frequently encountered in clinical practice, the population-based incidence and trends remain unknown, and the long-term outcomes are incompletely characterized. Methods: We prospectively recruited residents of Olmsted County, Minnesota, who experienced an event associated with a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 34 publications
5
74
1
4
Order By: Relevance
“…Furthermore, because this study focused on coronary artery disease, patients with myocardial injury, such as Takotsubo cardiomyopathy or pulmonary embolism, were intentionally excluded at the time of entry. This may have affected the lower proportion of Type 2 MI compared with previous observational studies [19,20,25].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Furthermore, because this study focused on coronary artery disease, patients with myocardial injury, such as Takotsubo cardiomyopathy or pulmonary embolism, were intentionally excluded at the time of entry. This may have affected the lower proportion of Type 2 MI compared with previous observational studies [19,20,25].…”
Section: Discussionmentioning
confidence: 79%
“…A multicenter study from 5 European countries, APACE, showed that the update of UDMI increased the number of newly diagnosed Type 2 MI patients reclassified in UDMI 2012 by 114% (comparison with UDMI 2007) in the same MI patient group [18]. A community-based study in the United States found that a dramatic reduction in Type 1 MI from 2003 to 2012 resulted in similar incidence of Type 1 and Type 2 MI [19]. Even in a recent investigation restricted to adults aged 50 years and younger, the ratio of Type 2 MI was as high as 32% (the actual proportion was 37%, if the patients with myocardial injury were excluded) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Raphael et al recently showed that underlying mechanism of the supply/demand imbalance affects long-term outcome, and further investigation is needed to clarify whether the distribution of mechanisms differs by sex. 16 Both men and women with type 2 MI have a poor prognosis. Our study showed that during the follow-up period 50% and 45% of men and women, respectively, died following type 2 MI.…”
Section: Coronary Artery Disease Discussionmentioning
confidence: 99%
“…Raphael et al recently showed that underlying mechanism of the supply/demand imbalance affects long-term outcome, and further investigation is needed to clarify whether the distribution of mechanisms differs by sex. 16 …”
Section: Discussionmentioning
confidence: 99%
“…This study shows a decrease in the incidence of major CVD events in successive population-based incident RA cohorts. This improvement appears to be largely driven by an over 50% decline in the incidence of MI in patients with RA onset in 2000s versus 1980s, concomitant with the declining incidence of MI in the general population (22). Coronary revascularization procedures are increasingly widespread therapeutic interventions for patients with CAD with potential impact on subsequent CVD events (25,26).…”
Section: Discussionmentioning
confidence: 99%